As práticas de intervenção precoce no estado de São Paulo - Marini, Bruna Pereira Ricci (Universidade Federal de São Carlos, 2017)
Early Intervention is constituted as an important tool for prevention, identification and intervention in conditions that offer risks to child development. Since the emergence of the first programs dating back to the 1960s, there were a number of conceptual and theoretical developments which culminated in the recognition of the systemic, ecological and family-centered model, as it produces better effects. In Brazil, the Early Intervention practices appear to develop highly focused on the needs of children, prioritizing interventions guided in their problems and developed from a rehabilitative model. It also observes that, despite the relevance of the theme, the scientific literature is scarce, which points to the need for further investigation. In this context, this study aimed to identify the practices developed by the Early Intervention services for children from zero to five years, in the state of São Paulo. This is a cross-sectional, descriptive and exploratory study with a qualitative approach. Participants were selected through non-probability sampling for convenience, in the case of professional staff working in services for children between zero and five years, located in the area covered by the Programa São Paulo pela Primeiríssima Infância. The study was developed in two stages, the first identification and characterization of early intervention services and the second identification of early intervention practices developed for services previously selected from the first stage. Data were collected through questionnaires (first stage) and interview (second stage). For the analysis of data from the questionnaires was used the methodology of descriptive statistics and analysis of the interviews content analysis methodology, the thematic analysis mode. The results of this study corroborate with the descriptions in the national scientific literature showing that Early Intervention practices remain being developed within the rehabilitation model, geared to the deficits presented by the children. In this context, the participation of families in the services proved to be limited because of the hegemonic role played by professionals in relation to the intervention process. It also revealed the existence of differences between the recommended practices in the child care networks and those that, in fact, are developed by the services. Regarding the existence of practices implemented in the natural context of the child, the results showed that these have been limited to observations and guidelines. Finally, the study identified a number of gaps in the process of training and continuing education of professionals that working in Early Intervention, a factor that can directly impact on the quality and the implemented practice model. From these results, the possibilities and challenges for the approximation between current practices and those recommended internationally are discussed, based on IP literature and national child care policies.
Keywords: Desenvolvimento infantil; Intervenção precoce; Família; Serviços de intervenção precoce; Child development; Early intervention; Childhood; Family; Early childhood intervention services; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL